REGISTERIAL REPRESENTATION IN KARONESE MANTRA TEXT (LINGUISTICA, 2022)
The objectives of this study were conducted to find the registerial representation implied in Karonese mantra text in erpangir ku lau, and to discover the registerial representation in the karonese mantra text. This research was conducted by descriptive qualitative method. The finding of this study showed that the registerial reprsentaion are implied in karonese mantra text in Erpangir ku lau were Field, tenor and Mode. Field is realization of experiential meanings; these experiential meaning are realized through transitivity pattern, from 6 kinds of total process in transitivity there is only five types were implied in karonese mantra text, they were material, relational ,mental, verbal and behavioral process in this text. the tenor is the realization of Interpersonal meanings; these interpersonal meaning through the mood, there just 2 kinds from 3 total mood that found in karonese mantra text, they were declarative and imperative. In Mode that realizes in Theme pattern found that all of 4 types in Theme were implied in this text. This theory also related to the register language, the Frozen and formal discovered in karonese mantra text.